Perdas de nitrogênio por volatização de amônia e eficiência da adubação nitrogenada na cultura do arroz irrigado - Duarte, Francisco Mendoza (2006)
This work was developed using two greenhouse and two field experiments, during 2004/2005 agricultural season at the Federal University of Santa Maria, Rio Grande do Sul state. The objective was to evaluate nitrogen loss by ammonia volatilization at different soil water content and to evaluate nitrogen fertilization efficiency with different urea application based on flooding time. The first greenhouse experiment was developed with N-urea application at different soil water status (dry, humid, saturated, and ponding water) and a treatment without nitrogen application, in a completely randomized experimental design whit four replications. The treatments were applied on 5 kg soil pots with ammonia collectors to quantify nitrogen volatilized. The second greenhouse experiment was developed with N-urea application based on flooding times (15, 10, 5, and 1 day before flooding and 1 day after flooding) and a treatment without nitrogen application, in a completely randomized experimental design with four replications. The two field experiments were developed with five different times of urea application based on flooding times (one with 7, 4, and 1 day before flooding and 1 and 3 days after flooding and another with 10, 6, and 3 days before flooding, at flooding, and 2 days after flooding) and a treatment without nitrogen application, in a randomized block design with four replications. In the second greenhouse experiment and two field experiments, green and dry matter production and nitrogen uptake were evaluated, while grain production was also evaluated in the two field experiments. The urea application on ponding water did not prevent nitrogen loss by ammonia volatilization and the first nitrogen application had higher efficiency when applied before flooding, even though the grain production was not affected by urea application time.